Itraconazole Loaded Micelle Based on Methoxy Poly(Ethylene Glycol)-Poly(D, L-Lactic Acid) for Ocular Drug Delivery: In vitro and in vivo Evaluation - He J; Yang J; Liang Z; Zhang Z; Pu G; Dong F; Lu P; Xia H; Zhang J (International Journal of Nanomedicine)
Jijun He,* Jingjing Yang,* Zhen Liang, Zhen Zhang, Guojuan Pu, Fudan Dong, Ping Lu, Huiyun Xia, Junjie Zhang Henan Eye Hospital, Henan Provincial People’s Hospital, Zhengzhou University People’s Hospital, Zhengzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junjie Zhang, Email zhangjunjie@zzu.edu.cnPurpose: This study aimed to develop itraconazole (ITZ)-loaded polymer micelles using methoxy poly(ethylene glycol)-poly(D, L-lactic acid) (mPEG-PDLLA) as a carrier to improve the ocular bioavailability of ITZ after topical administration.Methods: ITZ-loaded mPEG-PDLLA micelles (ITZ-M) were prepared using the thin-film dispersion method and were characterized by droplet size (DS), zeta potential (ZP), polydispersity index (PDI), morphology, entrapment efficiency (EE%), and critical micelle concentration (CMC). In vitro drug release from ITZ-M, the storage stability and cytotoxicity in human corneal epithelial cells (HCECs) were studied. In vivo transcorneal permeation of micelles labeled with coumarin 6 (C6) was observed using two-photon confocal microscopy, in vivo ocular irritation and pharmacokinetics in rabbit eyes were investigated.Results: The ITZ-Ms were uniform spherical particles with DS of 18.79 ± 0.16 nm and narrow distribution (PDI of 0.037 ± 0.019), the EE% was nearly 100%, and the CMC of the micelles was 0.083mM. Approximately 60% of the drug was released from the ITZ-M within 72 h, which was significantly higher than that released from the ITZ suspension. The results of the stability study and cytotoxicity assays demonstrated that ITZ-M possessed good physical stability at 4°C and have no toxicity to HCECs. Transcorneal studies indicated that the fluorescence intensity (FI) was mostly enriched in the corneal epithelium, which was reduced in the stroma. The FI in the epithelium and stroma for C6 micelles was much stronger than that in the C6 suspension. Ocular irritation evaluation revealed that ITZ-M was well tolerated. Ocular pharmacokinetic analysis indicated that the area under the curve (AUC0-240min) values in the cornea and conjunctiva of rabbit eyes treated with ITZ-M were approximately 410.9- and 2.3-fold higher, respectively, than those treated with ITZ suspension.Conclusion: This study provides a potential formulation of ITZ for the treatment of fungal keratitis with good tolerability and improved ocular bioavailability. Keywords: fungal keratitis, itraconazole, methoxy poly(ethylene glycol)-poly(D,L-lactic acid), polymeric micelle, ocular pharmacokinetic